Rolando García’s “Complex Systems Theory” and its relevance to sociocybernetics - Becerra, Gaston; Amozurrutia, José Antonio (Journal of Sociocybernetics, 2015)
Complex Systems Theory (“TSC” for its Spanish acronym) by the Argentine-Mexican physicist and epistemologist Rolando García (1919-2012) provides a comprehensive framework to approach complex issues or complex problems requiring an interdisciplinary approach. In this work its theoretical and conceptual framework is summarized and exemplified through case studies. TSC proposed methodology and constructivist epistemology are also briefly introduced. Furthermore, its relevance for sociocybernetic is discussed on a programmatic level.